Investor attention in the Brazilian stock market: essays in behavioral finance - Guzella, Marcelo dos Santos (2020)
We developed three essays regarding the impact of the investor attention on the Brazilian stock market. Attention is a cognitive resource of great relevance and has been increasingly studied in research related to behavioral finance. It has a crucial role in processes such as buying and selling assets, absorption of information and risk management. Firstly, we evidenced that attention transmits market efficiency for being a requirement for the discovery of released information, and this effect is more associated with professional attention. After that, we verified that attention, particularly the one of retail investors, is capable of inducing volatility to the market due to a price pressure by noise trading. Finally, we verified that the volatility of prices is less asymmetric when investors are more attentive to financial information. We measured attention through the volume of searches for financial information over the Internet, particularly the queries performed using Google and Bloomberg. These indicators have properties that allow several approaches that were limited or impossible before they were available. All the results are robust to different methodologies and specifications. Among other innovations, this study is a pioneer in isolating the effect of retail and professional attention on the market efficiency and asymmetry. Our findings contribute to a better understanding of the influence of aggregate psychological aspects on stock prices and open promising venues for research ideas in many fields.